KELUARGA KRISTIANI SEBAGAI GARAM DAN TERANG DUNIA: SEBUAH KAJIAN MORAL - Antonius Virdei Eresto Gaudiawan (Lembaga Penelitian STKIP Widya Yuwana, 2019)
Family is an ecclesia domestica. Every family have a duty to be the salt and the light of the world. This is the most suitable way for every christian more over christian family to receive the kingdom of God that has come to this world. This is a way of discipleship. In the global age, christian families confront many difficulties to be the salt and the light of the world such as the dy namics of success, ethic, hyperconnection, and economic. That's why every christian families should increase their consciousness about world and theirselves, be a struggler of christian values, using gadget as media to preach the go pel, and living an intimate relation in their ownfamily.